(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Emerging innovations have changed the landscape of HR and posed many challenges for organizations, such as integration of HR technology and automation with existing HR systems, lack of skills, data quality, and data infrastructure. There is a lack of understanding of leveraging AI-powered people analytics and how metaverse can be used to optimize HR functions. Leveraging secondary data sources such as Industry reports, corporate data, industry insights, and existing studies, this study seeks to explore the potential of AI-driven people analytics and metaverse and to propose a theoretical framework for understanding and leveraging people analytics, AI-powered people analytics, and metaverse and to optimize the workforce management. This study submits a comprehensive model for understanding the role of people analytics through case study synthesis and thematic analysis of multiple reports and surveys. This study found that AI-driven insights are applied to almost every domain of HR such as talent acquisition, training and development, performance management, employee well-being, and mental health, HR strategies and decision-making. This study offers theoretical contributions and practical implications for people analytics and provides valuable insights for researchers and HR professionals.